Indigenous Education in Brazil—The Case of the Bare People in Nova Esperança: Transition to Work and Sustainability - Giovanna Campani (Social Sciences)
The paper presents the institutional framework of the Indigenous Schools in Brazil it raises the issues presented by the relationship between school as institution and patterns of indigenous culture transmission, given the complex structure of the indigenous population in Brazil, divided into more than 306 ethnic groups, and the historical intercultural relations established with the European colonizers. The second part describes a specific Indigenous school located in the community of Nova Esperança, whose members belong predominantly to the Baré ethnic group. The village overlooks the Cuieiras River—a tributary of the Rio Negro—and is 80 kilometers (km) away from Manaus, the capital of the State of Amazonas. Nova Esperança is called “Pisasú Sarusawa” in Nheengatu, Ñe’engatu o Ñeengatu, known as the “general language” of the Amazonas. An interview with Joarlison Garrido, the school director, deals with the question of the usefulness of indigenous education in the school-to-work transition. According to Joarlison Garrido, indigenous education can promote community development, employment, and sustainability. This positive result is possible thanks to the special location of Nova Esperança within the Puranga Conquista Sustainable Development Reserve (RDS), managed by the government of the State of Amazonas. In this precise context, indigenous education represents a tool to ensure the new generations of Baré have a successful transition from school to work and an employment, namely through the projects of sustainable development that are foreseen for the area. Moreover, as Joarlison points out, sustainability is currently a global issue: consequently, the experience of Nova Esperança is at the same time local and part of a global trend. The Indigenous schools represent a great potential to develop original pedagogical practices in the field of intercultural education that can impact the transition from school to work not only in Brazil but in various contexts where Indigenous Peoples live. The case of the community of Nova Esperança is an example of this direction.